2012
DOI: 10.1136/ebmed-2011-100065
|View full text |Cite
|
Sign up to set email alerts
|

Payer decision-making with limited comparative and cost effectiveness data: the case of new pharmacological treatments for gout

Abstract: Although febuxostat trials included allopurinol as a comparator, methodological limitations make comparative effectiveness evaluations difficult. However, when available trial data were input to a decision analytic model, the authors found that a significant reduction in febuxostat cost would be required in order for it to dominate allopurinol in cost effectiveness analysis. This case exemplifies the challenges of using clinical trial data in comparative and cost effectiveness analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A study by Meltzer et al (2012) found that a significant reduction in febuxostat drug cost would be required for it to dominate allopurinol. 19 Although, the authors found febuxostat to be a cost-effective option, they did not account for relevant health care resource costs typically associated with gout patients.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by Meltzer et al (2012) found that a significant reduction in febuxostat drug cost would be required for it to dominate allopurinol. 19 Although, the authors found febuxostat to be a cost-effective option, they did not account for relevant health care resource costs typically associated with gout patients.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…19 Although, the authors found febuxostat to be a cost-effective option, they did not account for relevant health care resource costs typically associated with gout patients. For instance, febuxostat incurs additional costs for liver function test abnormalities and the expected cost for 20 Although this study found fewer gout flares, fewer CKD stage 5 patients with gout, and reduced overall costs, the authors accounted for a specific subgroup of gout patients, thereby reducing the applicability of their study findings.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations